Understanding young immigrant Chinese consumers' freshness perceptions of orange juices: A study based on concept evaluation. (March 2016) - Zhang, Ting; Lusk, Karen; Mirosa, Miranda; Oey, Indrawati
Highlights: Perceived freshness involved interactions of sensory sensations and non-sensory attributes. Perceived freshness was related to an overall notion of healthy and natural. Level of closeness to the perceiving orange-like sensory properties defined perceived freshness. 'Sensory properties-driven', 'pulp lover' and 'packaging information-driven consumers' were identified. Abstract: Freshness is a multidimensional attribute commonly encountered in everyday life and particularly in association with food. It awakens certain expectations from consumers, as it is a critical variable that affects the food quality and acceptability. The aim of this research was to identify sensory and non-sensory factors contributing to young immigrant Chinese consumers' freshness perceptions of orange juices. Two focus groups were undertaken, where participants ( n  = 19) evaluated freshness of 20 orange juices and their corresponding packages. The qualitative data from these focus groups was combined with the results from a wide-ranging review of existing literature on orange juice characteristics as well as related consumers' perceptions. From this, a set of 60 statements was derived with the purpose of representing the whole spectrum of possible viewpoints that young immigrant Chinese consumers might have about freshness. To obtain a holistic understanding of freshness, these statements were then used for subsequent sorting exercises using Napping and Q methodology ( n  = 20). Results showed that perceived freshness was related to an overall notion of healthy and natural. The young immigrant Chinese consumers defined freshness as a level of closeness to the orange, perceiving orange-like sensory qualities as fresh. Results also showed that freshness perceptions were greatly influenced by non-sensory attributes. Three distinct consumer perspectives were identified, with consumers in each of these perspectives holding homogeneous viewpoints about freshness. The new insights obtained from this research are important for food companies in determining long-term new product developments and in developing the marketing mix for products that are marketed on the freshness attribute.